PENGETAHUAN DALAM MENGONTROL KADAR GULA DARAH PASIEN DIABETES MELITUS TIPE 2 (DMT2) - Andriani, Wiwiek Retti; Handayani, Intan Dwi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Diabetes mellitus is a chronic disease characterized by unstable blood sugar levels. One of the causes of instability in blood sugar levels in people with diabetes mellitus is the lack of knowledge caused by the lack of information obtained. The purpose of the study was to provide nursing care to clients with type 2 diabetes mellitus with knowledge deficits in controlling blood sugar levels at the Jambon Ponorogo Health Center. The research method applied is descriptive qualitative in the form of a case study. Data collection techniques through interviews and questionnaires KDDQ (Knowledge of Diabetic Diet Questionnaire). The results of the study found that the client had a low level of knowledge, behavior was not as recommended, the client asked about diabetes mellitus, especially in controlling blood sugar levels. The nursing diagnosis established is a knowledge deficit. Nursing interventions according to SIKI: Health education that has been implemented for 3 days using lecture, question and answer, and discussion methods delivered through video media and leaflets. The result criteria set are that the level of knowledge increases with the indicator that the client is able to answer the KDDQ questionnaire and achieves a good level of knowledge, is able to explain the material presented again, and is able to apply the material in everyday life. After being given implementation for 3 days, the patients knowledge can be evaluated, which was initially <60% in the poor knowledge category into a good knowledge category >80%. Health Education using videos and leaflets can increase the knowledge of Type 2 DM clients and it is hoped that clients will be able to control their blood sugar levels by changing their behavior in regulating eating patterns in daily life according to the education provided.